Moving deserts: stories of mobilities and resilience from Turkana County, a Kenyan desertscape - Semplici, G (2019)
This thesis is about resilience, drylands, and pastoralism. It aims to enhance our understanding of the meanings of resilience from the perspective of pastoral communities in drylands and in the context of their everyday lives. It draws on the case of Turkana herders living in Kenyan’s northern drylands, a place of “resilience making” for the international community. Threatened by recurrent droughts, security issues, and precarious living, Turkana County is the perfect laboratory for international organisations interested in “building resilience” to shocks and disasters, and in turn also a compelling case for a thesis which hopes to bring a more grounded, nuanced, and rooted understanding of resilience in drylands.